Reviving the Legacy of Classical Islamic Scholars in the Digital Era: A Study on Ulil Abshar Abdalla’s Ngaji Tasawuf Online - Mursalat, Mursalat (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study explores the role of Ngaji Tasawuf Online in preserving classical Islamic knowledge, focusing on the digital transmission of Ihya’ Ulumuddin by Imam Ghazali, led by Ulil Abshar Abdalla. In the context of advancing information technology, digital recitation emerges as an adaptive method for sustaining spiritually rich traditional teachings. Using a qualitative descriptive approach, data were collected through documentation studies and observations of online sessions shared via platforms like Facebook, YouTube, and Spotify. The findings indicate that online recitation enhances accessibility, particularly for individuals constrained by time and location. Moreover, social media facilitates real-time interaction between teacher and participants, fostering a dynamic, though virtual, learning environment. While challenges remain in preserving the depth of classical pedagogy in digital formats, online recitation effectively maintains spiritual traditions in a way that aligns with modern life. Ultimately, it serves not only as a means of knowledge transmission but also as a platform for reinforcing the relevance and depth of classical Islamic teachings today.